An analysis of stress over a bonded repaired stiffened panel / Ramzyzan Ramly and Wahyu Kuntjoro (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2007)
Damages in aircraft structures are classified as negligible or intolerable. Intolerable damage should be repaired to maintain airworthiness of the aircraft. One of the damages covered in this paper is crack damage and the repair on it. The damage location in this paper is on the skin next to the stringer section. Most damage repair methods and procedures are prescribed in the Structural Repair Manual (SRM). This paper presents strength/stress analysis on the section (stiffened panel) before damage, after damage, and after repair using bonded patch. Finite Element Analysis (FEA) software called ANSYS was used. An experimental method was used to validate the FEA method. The results of the analysis showed that the strength of the repaired structure was restored. Both methods showed agreement in the results pattern.